Respuesta :
True
You need to subtract 2x^2 from both sides and add 7x to both sides. This leaves:
3x^2 + 10x -8 = 0
You need to subtract 2x^2 from both sides and add 7x to both sides. This leaves:
3x^2 + 10x -8 = 0
Answer:
Answer is True.
Step-by-step explanation:
Given expression is [tex]5x^2+3x-8=2x^2-7x[/tex]
Here, Standard form is in which all terms are on LHS and terms should be in decreasing order of degree.
Consider,
[tex]5x^2+3x-8=2x^2-7x[/tex]
Add both sides by 7x, we get
[tex]5x^2+3x-8+7x=2x^2-7x+7x[/tex]
[tex]5x^2+10x-8=2x^2[/tex]
Subtract 2x² from both sides, we get
[tex]5x^2+10x-8-2x^2=2x^2-2x^2[/tex]
[tex]3x^2+10x-8=0[/tex]
Therefore, Answer is True.